2014
DOI: 10.1097/rli.0000000000000055
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Prostate Cancer With Dynamic Contrast-Enhanced Computed Tomography Using an En Bloc Approach

Abstract: OBJECTIVES The aim of this study was to assess the performance of dynamic contrastenhanced computed tomography of the prostate in patients with biopsy-proven prostate cancer. MA-TERIAL AND METHODS A total of 46 male patients (median age, 65 years; range, 49-73 years) with biopsy-proven prostate cancer underwent an en bloc computed tomography perfusion (CTP) scan of the prostate before surgery. The perfusion parameters mean transit time (MTT), blood flow (BF), and blood volume (BV), as well as the microvessel d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 41 publications
(30 reference statements)
1
13
0
Order By: Relevance
“…They found higher BF and BV in high-grade PCa (Gleason score >7) rather than in intermediate-(Gleason score=7) and low-grade (Gleason score <7) tumors. Similar results were found recently by Huellner et al [11] using an en-bloc approach. In our study, in which we used a sector-wise approach, we have found correlation between Gleason score and BV but not with BF.…”
Section: Frequency (%)supporting
confidence: 81%
See 4 more Smart Citations
“…They found higher BF and BV in high-grade PCa (Gleason score >7) rather than in intermediate-(Gleason score=7) and low-grade (Gleason score <7) tumors. Similar results were found recently by Huellner et al [11] using an en-bloc approach. In our study, in which we used a sector-wise approach, we have found correlation between Gleason score and BV but not with BF.…”
Section: Frequency (%)supporting
confidence: 81%
“…In our study, in which we used a sector-wise approach, we have found correlation between Gleason score and BV but not with BF. BV is consistently reported to be associated with PCA grading and/or vascularity in different study populations and in CTP studies using different technical approaches (9,11,22,26 and present study). These results raise the question for a potential role of BV for non-invasive PCa characterization via determining tumor aggressiveness.…”
Section: Frequency (%)mentioning
confidence: 91%
See 3 more Smart Citations